A pilot mixed-methods evaluation of MS INFoRm: a self-directed fatigue management resource for individuals with multiple sclerosis. Issue 2 (June 2018) - Akbar, Nadine; Turpin, Karen; Petrin, Julie; Smyth, Penny; Finlayson, Marcia
Abstract : Fatigue management interventions for individuals with multiple sclerosis (MS) often feature structured programmes requiring repeated, in-person attendance that is not possible for all individuals. We sought to determine whether MS INFoRm, a self-directed fatigue management resource for individuals with MS, was worth further, more rigorous evaluation. Our indicators of worthiness were actual use of the resource by participants over 3 months, reductions in fatigue impact and increases in self-efficacy, and participant reports of changes in fatigue management knowledge and behaviours. This was a single-group, mixed-methods, before–after pilot study in individuals with MS reporting mild to moderate fatigue. Thirty-five participants were provided with MS INFoRm by a USB flash drive to use at home for 3 months, on their own volition. Twenty-three participants completed all standardized questionnaires, semi-structured interviews and study process measures. Participants reported actively using MS INFoRm over the 3-month study period (median total time spent using MS INFoRm=315 min) as well as significantly lower overall fatigue impact (Modified Fatigue Impact Scale: t =2.6, P =0.01), increased knowledge of MS fatigue ( z =−2.8, P =0.01) and greater confidence in managing MS fatigue ( z =−3.3, P =0.001). Individuals with significant reductions in fatigue impact also reported behavioural changes including tracking fatigue, better communication with others, greater awareness, improved quality of life and being more proactive. This study provides evidence that further rigorous evaluation of MS INFoRm, a self-directed resource for managing fatigue, is worth pursuing.